Exploration of gaps and challenges in managing burn injury at district and sub-district government health care facilities in Bangladesh. Issue 1 (January 2020) - Biswas, Animesh; Abdullah, Abu Sayeed Md.; Deave, Toity; Dalal, Koustuv; Mashreky, Saidur Rahman
Highlights: Lack of training of health care providers to manage burns in the district and below. Constraints to treat burn patients in the district and below facilities are persist. Traditional practices in the community is a big challenge in burn management. Mass awareness and campaign are essential at the community to prevent burn. Abstract: Background: Burn injury is one of the leading cause of mortality and morbidity worldwide. In developing countries like Bangladesh, burn is one of the leading causes of illness, disabilities and deaths. More than 365, 000 people are injured every year by electrical, thermal and other causes of burn injuries where 27, 000 people needed hospital admission and over 5600 people died. Emergency management of burn at the facility level can reduce the severity of burn injuries and improve overall survival. The study has explored the health care providers' views on gaps and challenges in management of burn injury at the facilities district and sub district health facilities in Bangladesh. Methodology: A qualitative study was conducted during the period in July 2015. In-depth interviews (n = 19) were performed with the doctors and nurses working in the three district government hospitals and seven sub-district (upazila) government health facilities. Thematic analysis was performed on different themes. Results: Health care providers mentioned that the people are coming to the facilities usually, hours after the incidence. Before visiting the facilities, the burn victims mostly seek treatment from the traditional healers or form village doctors (quack) or from the local pharmacy, over the counter. Family waited until they felt that the patient may not survive. It has identified that delaying in decision making and transferring the patient to the health facility are the key challenges identified by the doctors and nurses when they attended any burn patients in their facility. Moreover, use of different traditional infectious agent in burnt areas from their home make the burn surface more damage. While as, deficiency of adequate supplies, logistics and adequate trainings for the health workers in the facility create much more difficulties to treat a burn patient at primary or secondary health care centers. Conclusion: Burn patients are maltreated in the community before coming to the healthcare facility in most of the cases. The community has misperceptions on burn management which delay the proper management in the facility. Readiness of the facility on the other hand is a big challenge. In order to consistent in burn care in Bangladesh, its equally important to build knowledge and awareness among the community on burn prevention and their role. Like this, readiness of the facilities in time will build confidence in community, thus in turns, will save thousands of lives from burn injury in Bangladesh.